Students’ System Thinking Skills through Project Based Learning with STEM Approach (PJBL-STEM): A Quasi-Experimental Study - Maya Shinta Saqila; Windi Anggraini; Ahmad Suryadi; Iwan Permana Suwarna (Jurnal Pendidikan Fisika, 2025)
Students have difficulty understanding physics concepts because they cannot connect them with everyday life. As a result, they study concepts separately and do not understand the relationships between concepts, especially on the topic of renewable energy, which are interconnected and play an important role in future life. This study aims to analyze the influence of the STEM-based Project-Based Learning model on students' system thinking abilities. A quantitative approach was used with a quasi-experimental design in the form of a Nonequivalent Control Group Design. The sample consisted of 62 tenth-grade students divided into experimental and control classes. The experimental class received the PJBL-STEM treatment, while the control class used the Problem Based Learning model. The highest improvement was observed in the coherent indicator, while the lowest improvement was in the intermediate indicator. These findings indicate that PJBL-STEM is effective in enhancing students' system thinking abilities, with an N-Gain value of 0.76 in the high category. This research is beneficial as an alternative learning strategy that can develop students' thinking skills and contribute to designing learning that is relevant to students' real-life contexts.